ANALISIS PENGARUH KARAKTERISTIK GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Infrastruktur yang Terdaftar Di Bursa Efek Indonesia) - Olivia Yuni Ayu Wulandari; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of the characteristics of good corporate governance as measured by the proportion of the board of commissioners, the proportion of independent commissioners, the proportion of the audit committee, institutional ownership, and disclosure of social responsibility on the financial performance of infrastructure companies as measured by return on equity (ROE). The sample in this study were infrastructure companies listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling technique used the purposive sampling method by applying certain criteria to obtain 80 samples consisting of 16 companies. The method used in this research is quantitative method with classical assumption test and multiple linear regression test. The results showed that the characteristics of good corporate governance in the form of the proportion of the board of commissioners and the disclosure of social responsibility (CSR) affect the company's financial performance which is reflected in the return on equity (ROE). Meanwhile, the proportion of independent commissioners, the proportion of audit committees, and institutional ownership have no effect on the company's financial performance.